Efek STEM Dalam Pembelajaran Sains Terhadap Keterampilan Abad 21: Meta Analisis - Novianti, Baiq Aryani; Lasmawan, I Wayan; Suharta, I Gusti Putu (Kappa Journal, 2023)
21st-century skills are one of the skills that students must master. Curriculum 2013 which trains and develops 21st-century skills can be implemented by applying STEM in science learning. The method of this study is to analyze journal articles obtained through online journals. This study analyzed 20 journals published from 2016 to 2022 and calculated the effect size which included 16 national journals and 4 international journals. The results of the data analysis show that at the elementary, junior high, and senior high school levels, the impact of STEM on science learning at all levels of education is relatively high. The implementation of STEM in Science Learning has an impact on 21st-century skills such as critical thinking, creative thinking, communication, and collaboration